Adaptasi Instrumen Community Attitudes Toward The Mentally Ill (CAMI) Versi Bahasa Indonesia Menggunakan Metode Rasch Model - Wini Indriani; Devie Yundianto; Muhammad Khatami (Universitas Kristen Maranatha, 2025)
This study aims to validate the CAMI instrument developed for respondents in Indonesia using Rasch modeling. Community Attitudes Towards the Mentally Ill (CAMI) or community attitudes towards people with mental disorders refers to how society responds to someone with a mental disorder. The sub-dimensions of CAMI are based on (1) authoritarianism, (2) benevolence, (3) social restrictiveness, and (4) community mental health ideology. This instrument was tested on 255 respondents spread across various regions using a Google form. Of the 255 respondents obtained, only 222 respondents were used in the Rasch modeling analysis because 33 respondents needed to meet the person fit test requirements and had to be discarded. The results of the study indicate that CAMI has good psychometric characteristics for measuring community attitudes toward people with mental disorders. All Rasch modeling assumptions are met. Respondent reliability of 0.62, item reliability of 0.99, and instrument reliability of 0.66 indicate fairly good internal consistency of the Indonesian version of CAMI. Based on these findings, public attitudes towards people with mental disorders in Indonesia can be measured using this instrument.